The Contribution of Muslim Women Australia in the Domestic and Family Violence Space: Victim-Survivor Perspectives from the COVID-19 Pandemic - Aftab, Amira; Jones, Balawyn; Krayem, Ghena (2024)
This article examines the way faith and Islamic values underpin the agency and work of Muslim women in providing domestic and family violence (DFV) support services. Focusing on the role and impact of Muslim Women Australia within the DFV space in the Australian context, this article demonstrates the way Muslim Women Australia utilises faith as a tool for empowerment. It illustrates the way that—despite governmental reforms that required transition from specialised to generalist DFV services—Muslim Women Australia, via their DFV service Linking Hearts, has maintained a strong commitment to providing culturally and religiously appropriate support. Drawing on fieldwork, this article explores the intersection of Muslim women’s agency, faith, and role as DFV service providers, to demonstrate the importance of culturally competent DFV support services within diverse communities. Through interviews with clients (victim-survivors) who accessed Linking Hearts services during the COVID-19 lockdowns, this article highlights the way the Islamic values of advocacy, agency, and dignity underscore the Linking Hearts model to effectively provide culturally and religiously competent support to all clients regardless of their personal beliefs and values.
Keywords: Covid-19; Islamic values; Domestic Violence; Agency; Muslim Women